Dengue Management in Triage using Ultrasound in children from Cambodia: a prospective cohort study - Timothy Gleeson; Yos Pagnarith; Eang Habsreng; Robert Lindsay; Michael Hill; Alexandra Sanseverino; Viral Patel; Romolo Gaspari (Elsevier, 2022)
Summary: Background: Dengue is a mosquito-borne viral infection with increasing global prevalence. It is endemic in more than 100 countries, with a heavy burden in Asia. Ultrasound findings including gallbladder wall thickening, ascites, and pleural effusions secondary to plasma leakage have been described in dengue. We aimed to determine if the presence of point-of-care ultrasound findings early in suspected dengue could predict clinical worsening in ambulatory pediatric patients. Methods: We did a prospective, single-blinded, observational cohort study at a children's hospital in Siem Reap, Cambodia during periods of dengue outbreak. Ambulatory patients were screened and children ages > 3 month and ≤ 16 years with suspected acute, non-severe dengue were enrolled. Subjects had chest and abdominal ultrasound exams. Independently, subjects were evaluated by a blinded physician who determined a treatment plan as per usual practice. Follow-up was conducted 7-10 days after the initial visit. Analysis of ultrasound findings was performed to determine their relationship with outcome measures including need for unplanned hospital visits or admissions. Findings: A total of 2,186 children were screened during periods of national dengue outbreak in Cambodia in consecutive years 2018-2019, and 253 children met eligibility criteria. Results showed patients with gallbladder wall thickening (> 3·0 mm) who were discharged had a significantly more likely need for unplanned visit or hospitalization than those with normal gallbladder wall, 67% (95% CI 44 - 84) versus 17% (95% CI 12 - 24), p < 0.0001. Subjects with any abnormal ultrasound finding were more likely to be directly admitted versus discharged upon initial presentation, 62·2% (95% CI 46.1 - 76.0) versus 19.5% (95% CI 14.8 - 25.4), p < 0.0001. Interpretation: Point-of-care ultrasound findings, particularly gallbladder wall thickening, in suspected early dengue can help predict disease progression in ambulatory patients. Ultrasound has potential to help guide management of suspected dengue patients and resource management during periods of dengue outbreak. Funding: Society for Academic Emergency Medicine Foundation.